2012
DOI: 10.2174/138161212799958440
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA G-Quadruplex Structures with Peptide Nucleic Acids

Abstract: Regulation of genetic functions based on targeting DNA or RNA sequences with complementary oligonucleotides is especially attractive in the post-genome era. Oligonucleotides can be rationally designed to bind their targets based on simple nucleic acid base pairing rules. However, the use of natural DNA and RNA oligonucleotides as targeting probes can cause numerous off-target effects. In addition, natural nucleic acids are prone to degradation in vivo by various nucleases. To address these problems, nucleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…12 In our previous work, we discovered that short, guanine-rich PNA oligomers could invade and bind to plasmid DNA (Figure 1b). 13 We showed that invasion of duplex DNAdepends on PNA binding to its target sequence by Watson-Crick hydrogen bonding and on quadruplex formation of the displaced DNA strand. 13 Using PNA to promote quadruplex formation in this manner could work in conjunction with other strategies to target quadruplexes, such as small molecules 14 and anti-bodies for specific G-rich sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 In our previous work, we discovered that short, guanine-rich PNA oligomers could invade and bind to plasmid DNA (Figure 1b). 13 We showed that invasion of duplex DNAdepends on PNA binding to its target sequence by Watson-Crick hydrogen bonding and on quadruplex formation of the displaced DNA strand. 13 Using PNA to promote quadruplex formation in this manner could work in conjunction with other strategies to target quadruplexes, such as small molecules 14 and anti-bodies for specific G-rich sequences.…”
mentioning
confidence: 99%
“…13 We showed that invasion of duplex DNAdepends on PNA binding to its target sequence by Watson-Crick hydrogen bonding and on quadruplex formation of the displaced DNA strand. 13 Using PNA to promote quadruplex formation in this manner could work in conjunction with other strategies to target quadruplexes, such as small molecules 14 and anti-bodies for specific G-rich sequences. 15 Since there is a large structural diversity in DNA quadruplexes, combining strategies may also help improve specificity of targeting one type of G-quadruplex over others.…”
mentioning
confidence: 99%
“…Stabilization of such structures may result in alteration of gene expression and could potentially bring therapeutic benefits [3,4]. For this purpose, numerous small planar molecules that bind specifically to G-quadruplexes have been developed [5][6][7]; however, most of these small molecules bind G-tetrads via intercalation and base stacking that is nonselective among different types of quadruplexes.…”
mentioning
confidence: 99%
“…Another strategy to stabilize quadruplexes involves targeting the complementary strand of G-rich sequences with short peptide nucleic acids (PNA) [8][9][10] (reviewed in [3]). This approach is based on the earlier observation that PNA invade plasmid DNA more effectively at the target sequences that can form secondary structures, such as cruciforms [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation